More stable yet bimodal geodynamo during the Cretaceous superchron? - Florian Lhuillier; Stuart A. Gilder; Michael Wack; Kuang He; Nikolai Petersen; Brad S. Singer; Brian R. Jicha; Allen J. Schaen; Dylan Colon (Geophysical Research Letters)
Abstract We report palaeomagnetic and 40Ar/39Ar dating results from two sequences of basaltic lava flows deposited at the same locality in western China, yet separated in time by ~50 Myr: one set lies within the Cretaceous normal superchron at 112–115 Ma and a second at 59–70 Ma spanning the Cretaceous‐Palaeogene boundary. We find that magnetic field directions during the superchron exhibit bimodal populations: one with inclinations representative of a dipolar field and another with shallow inclinations that could reflect a more complex, multipolar field. However, the time‐dependent variability in field directions was 50% lower during the superchron than after, which implies greater field stability during the superchron. Our results suggest that episodes of less dipolar field behavior occurred within the Cretaceous superchron and raise the question whether a second, more multipolar, field state is more persistent than previously thought.